Review: Non-surgical artificial insemination and embryo recovery as safe tools for genetic preservation in small ruminants - Souza-Fabjan, J. M.G.; Oliveira, M. E.F. [UNESP]; Guimarães, M. P.P.; Brandão, F. Z.; Bartlewski, P. M.; Fonseca, J. F. (Elsevier, 2023)
Artificial insemination (AI) and in vivo embryo production (or multiple ovulation and embryo transfer, MOET) programs are both instrumental in accelerating the propagation of genetically and economically superior goats and sheep. The aim of this review was to present the current gestalt of non-surgical AI and embryo recovery (NSER) procedures in small ruminants. Small body size, precluding rectal palpation, and highly limited penetrability of the uterine cervix in ewes are the major reasons for the scarce use of non-surgical assisted reproduction techniques in this species. As a result, AI and embryo recovery techniques in sheep mainly involve laparoscopy or laparotomy (LAP). In does, however, the Embrapa method of AI allows for successful intrauterine deposition of semen, resulting in pregnancy rates from 50 to 80% under field conditions (>3 000 goats inseminated) when frozen-thawed semen is used. After the administration of prostaglandin F2α (PGF2α), non-surgical (transcervical) embryo recovery is also feasible in goats, with the cervical penetration rate approaching 100%. There is a paucity of information on the efficacy of non-surgical AI using frozen semen in sheep, but the results are satisfactory with fresh, cooled, or chilled ram semen. An application of the NSER technique in ewes has greatly improved over the last decade, and cervical penetration rates of ∼90% can be achieved when a hormonal cervical dilation protocol using PGF2α, oxytocin, and/or estradiol ester (e.g., estradiol benzoate) is applied. In some genotypes of sheep, sufficient cervical dilation can be induced without estradiol ester included in the protocol. Several studies indicated that recovery of transferable quality ovine embryos using NSER is comparable to that employing a ventral midline laparotomy, and NSER is evidently a method of choice when animal welfare is concerned. Considering both the number of retrievable embryos and animal well-being, the NSER is a viable alternative for surgical procedures. With further developments, it has the makings of a primary, if not exclusive, embryo recovery technique in small ruminants worldwide.
Keywords: Artificial insemination; Cervical dilation; Goat; Non-surgical embryo recovery; Sheep